1996
DOI: 10.1046/j.1365-313x.1996.09020243.x
|View full text |Cite
|
Sign up to set email alerts
|

The amino‐terminus of phytochrome A contains two distinct functional domains

Abstract: The N-terminus of phytochrome A is important for the structural integrity and biological activity of the photoreceptor. Mutational analysis of the N-terminus by two different strategies created two distinct photoreceptors, one inactive and the other hyperactive when expressed in transgenic tobacco, suggesting that this region has multiple functional domains. To identify critical residues within this N-terminal region, a series of smaller deletions of oat phytochrome A were created, designated NB (delta49-62), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 0 publications
5
71
0
Order By: Relevance
“…This truncated form of phytochrome also has slightly blue-shifted absorption peaks and slower dark reversion rates. Mutation of the first 10 Ser of phyA to Ala (all contained within the first 20 aa) or deletion of this region results in a mutant that is hypersensitive to light (Stockhaus et al 1992, Jordan et al 1996. Previous results had shown that Pr phytochrome is phosphorylated at the N terminus (Wong et al 1986).…”
Section: Structure and Function Analysismentioning
confidence: 99%
“…This truncated form of phytochrome also has slightly blue-shifted absorption peaks and slower dark reversion rates. Mutation of the first 10 Ser of phyA to Ala (all contained within the first 20 aa) or deletion of this region results in a mutant that is hypersensitive to light (Stockhaus et al 1992, Jordan et al 1996. Previous results had shown that Pr phytochrome is phosphorylated at the N terminus (Wong et al 1986).…”
Section: Structure and Function Analysismentioning
confidence: 99%
“…Such a scenario was suggested as a function of the serine-rich region at the extreme N terminus of phyA. When a mutant monocot phyA construct having this region deleted or replaced by alanine residues was expressed in transgenic tobacco plants, it produced a hyperactive photoreceptor (Stockhaus et al, 1992;Emmler et al, 1995;Jordan et al, 1995). In an attempt to explain this phenotype, it was hypothesized that phosphorylation of these serine residues might reduce the signaling activity of wild-type phyA.…”
Section: Regulation Of Phya Signaling By Spa1mentioning
confidence: 99%
“…The N-terminal extension domain (NTE; Neff et al, 2000) contains several Ser residues in phyA, which are subject to phosphorylation (Lapko et al, 1997(Lapko et al, , 1999. Experiments performed on modified phyA carrying Ser/Ala substitutions or deletions in the NTE proved that this region is necessary for correct intracellular localization, biological activity, and signal attenuation (Cherry et al, 1992;Stockhaus et al, 1992;Jordan et al, 1996Jordan et al, , 1997Casal et al, 2002;Trupkin et al, 2007).…”
mentioning
confidence: 99%